Self-healing in Nanocomposite Hydrogels - Haraguchi, Kazutoshi; Uyama, Kazuhisa; Tanimoto, Hisashi (Macromolecular rapid communications., 2011)
Polymer hydrogels with characteristics distinct from those of solid materials are one of the most promising candidates for smart materials. Here, we report that a nanocomposite hydrogel (NC gel) consisting of a unique polymer/clay network structure, can exhibit complete self‐healing through autonomic reconstruction of crosslinks across a damaged interface. Mechanical damage in NC gels can be repaired without the use of a healing agent, and even sections of NC gels separated by cutting, from whichever the same or different kinds of NC gel, perfectly (re‐)combine by just contacting the cut surfaces together at mildly elevated temperatures. In NC gels, the autonomic fusion of cut surfaces as well as the self‐healing could be achieved not only immediately after being cut but also after a long waiting time. Self‐healing: Nanocomposite (NC) gel with a unique polymer/clay network structure, can exhibit complete self‐healing through autonomic reconstruction of crosslinks across a damaged interface. Mechanical damage can be repaired without the use of a healing agent, and even sections separated by cutting, from whichever the same or different kinds of NC gel, perfectly (re‐)combine by contacting the cut surfaces at mildly elevated temperatures.